(3QSGdI aj MOhO GdYdhes - (3NjQ GdOjf Hf CMeO GdMfajs
(3ChdgG (B:s
(3GdMeO ddg MeOkG jdjb HfhGdg s
(3BNQgG (B:s
(3hMO GdNaGA (B: (3gh cd daX Nai eQGOg YdiGdeSGY HCi hLg cGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi hGdKdGKhfs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs